(untitled) (Research, Society and Development, 2020)
To carry out a bibliographic search on the prevalence of body dissatisfaction among adolescents. This is an integrative review. To search for and select the studies, the following databases were used: PubMed, Scielo and Science direct, totaling 10 articles, between the years 2016 to 2019. In all the studies it was verified that there is great dissatisfaction among teenagers, which may be due to the high social collection of friends, family and even the strong influence of the media in the search for the perfect body. It is necessary to implement programs that promote health, especially those related to the perception of body image, with emphasis on the life cycle of adolescence.